Meta-Analysis of Studies Evaluating the Effect of Cilostazol on Major Outcomes After Carotid Stenting. (February 2016) - Galyfos, George; Geropapas, Georgios; Sigala, Fragiska; Aggeli, Konstantina; Sianou, Argiri; Filis, Konstantinos
Purpose: To evaluate the effect of cilostazol on major outcomes after carotid artery stenting (CAS).Methods: A systematic literature review was conducted conforming to established criteria in order to identify articles published prior to May 2015 evaluating major post-CAS outcomes in patients treated with cilostazol vs patients not treated with cilostazol. Major outcomes included in-stent restenosis (ISR) within the observation period, the revascularization rate, major/minor bleeding, and the myocardial infarction/stroke/death rate (MI/stroke/death) at 30 days and within the observation period. Data were pooled for all studies containing adequate data for each outcome investigated; effect estimates are presented as the odds ratios (ORs) and 95 confidence intervals (CI).Results: Overall, 7 studies pertaining to 1297 patients were eligible. Heterogeneity was low among studies so a fixed-effect analysis was conducted. Six studies (n=1233) were compared for the ISR endpoint, showing a significantly lower ISR rate with cilostazol treatment after a mean follow-up of 20 months (OR 0.158, 95% CI 0.072 to 0.349, p<0.001). Five studies (n=649) were compared regarding 30-day MI/stroke/death (OR 0.724, 95% CI 0.293 to 1.789, p=0.484) and 3 studies (n=1076) were analyzed regarding MI/stroke/death within the entire follow-up period (OR 0.768, 95% CI 0.477 to 1.236, p=0.276); no significant difference was found between the groups. Data on bleeding rates and revascularization rates post ISR were inadequate to conduct further analysis.Conclusion: Cilostazol seems to decrease total ISR rates in patients undergoing CAS without affecting MI/stroke/death events, both in the early and late settings.